2014
DOI: 10.1021/ja504096m
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Conferred by Mutations Outside the Active Site through Alterations in the Dynamic and Structural Ensemble of HIV-1 Protease

Abstract: HIV-1 protease inhibitors are part of the highly active antiretroviral therapy effectively used in the treatment of HIV infection and AIDS. Darunavir (DRV) is the most potent of these inhibitors, soliciting drug resistance only when a complex combination of mutations occur both inside and outside the protease active site. With few exceptions, the role of mutations outside the active site in conferring resistance remains largely elusive. Through a series of DRV–protease complex crystal structures, inhibition as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 30 publications
11
111
0
Order By: Relevance
“…Analysis of crystal structures showed significant loss of interactions with DRV, while protease interactions were maintained with SQV. Molecular dynamic studies combined with crystal structures suggested L76V contributed to resistance by altering the overall enzyme dynamics [34]. Many distal mutations are classified as minor mutations that modulate the effects of major mutations.…”
Section: Diverse Mechanisms Of Resistancementioning
confidence: 99%
“…Analysis of crystal structures showed significant loss of interactions with DRV, while protease interactions were maintained with SQV. Molecular dynamic studies combined with crystal structures suggested L76V contributed to resistance by altering the overall enzyme dynamics [34]. Many distal mutations are classified as minor mutations that modulate the effects of major mutations.…”
Section: Diverse Mechanisms Of Resistancementioning
confidence: 99%
“…4, 23, 24, 3438 The mechanisms by which accumulated mutations affect the active site pocket and confer drug resistance are actively being studied. At present, the mechanism is believed to be multifaceted in that several aspects of protein function are altered such as protein flexibility through the hydrophobic sliding mechanism, 39, 40 protein stability, 41 or altered dynamics 42 and conformational sampling. 43 …”
Section: Introductionmentioning
confidence: 99%
“…This model also allows for the possibility that dynamics of each of the conformational states varies 67, 68 and, as mutations accumulate, the exchange rate among the states also varies. 42, 69 The four conformers of the proposed ensemble are shown in Figure 3 where the most noticeable change in protein structure involves a segmental motion of the β-hairpin flaps (also shown in Figure 1). Each conformer has been observed, to some degree, via X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…The protease variants with available DRV bound structures were SF-2 (PDB: 1T3R), L76V, V32I and V32I/L33F 17, 21 . The NL4-3 wild type and remaining variants were modeled based on the DRV-bound wild-type SF-2 structure.…”
Section: Resultsmentioning
confidence: 99%
“…This set included both intra-protease and protease–DRV hydrogen bonds. With an expanded panel of protease variants, relative to our earlier study 17 , the use of algorithms for detecting patterns of altered occupancies and identifying specific mutations that may underlie these alterations becomes essential. A combination of principal component analysis (PCA), to detect alterations, followed by hypothesis testing based on amino acid substitution at specific sites in the protease, was employed.…”
Section: Resultsmentioning
confidence: 99%